Postcolonial Studies: Hybridity and the Dominance of Whites over Blacks in American Poetry - Yuli Wahyuni; Diyah Iis Andriani (Fakultas Ilmu Budaya, Universitas Dian Nuswantoro, 2021)
This study aims to reveal the postcolonial issues contained in poetry I, Too by Langston Hughes and Incident by Countee Cullen. Both authors of these poems are figures from black people in America. The method used in this study is the qualitative method and literature study approach with the aim of exploring, describing, and understanding how the hybridity and dominance of whites over blacks in American poetry. The data source of this study is the words and phrases in both poems. The data containing postcolonial: hybridity and mimicry in the poems were characterized and analyzed using Homi K. Bhabha's theory (2007). Bhabha in his thinking tries to provide a